The main post-covid-19 neurological changes (Research, Society and Development, 2022)
Covid-19 was the pathogen that gave rise to a pandemic that is currently underway. Its consequences are still in the process of being understood by science, so this work seeks to understand the main neurological problems after Covid-19. General objective: Investigate the relationship between Covid and neurological changes, examining the path of the pathology and its impacts on the world. Methodology: Integrative literature review between the years 2020 and 2021, available in databases such as SciELO; PubMed and LILACS. Thus, a search was carried out in the virtual database, using the descriptors Covid-19, Neurological Changes and "neurological changes and covid" and "post covid symptoms" according to the descriptors in health sciences (DeCS) Results and discussions: Approximately 35% of the patients had neurological symptoms of headache, which was more commonly presented as bilateral and located in the frontal and occipital regions. Pereira and Callegaro (2020) identified demyelinating diseases of the central nervous system, which they found that Covid-19 poses a potential threat to patients with autoimmune diseases, including those with multiple sclerosis (MS) and neuromyelitis optic spectrum disorders. Conclusion: Several neurological changes due to Covid-19 infection, the current literature pointed to cognitive decline including the ability to remember, problems related to headache and olfactory disorders. Each case has a given treatment, where it is necessary to take into account that the appropriate treatments are still under development, as scientific knowledge about the impact of Covid on human health still requires further research on several fronts, elucidating case by case the due measures. With this, we suggest new studies, in order to create new research, to distinguish the main neurological manifestations that can later compromise individuals who were affected by Covid-19.